KEPASTIAN HUKUM SKEMA KONTRAK BAGI HASIL GROSS SPLIT TERKAIT INVESTASI MIGAS DI INDONESIA - Wienda Syafira Wibowo (2023)
Through Regulation of the Minister of Energy and Natural Resources Number 8 of 2017 the government made changes to the oil and gas production sharing contract system, from a cost recovery profit sharing contract scheme to a gross split profit sharing contract scheme. This change aims to increase investor interest in investing in the oil and gas sector in Indonesia. This study aims to determine legal certainty and also the impact of implementing a gross split production sharing contract scheme through normative juridical methods with library research methods. The results of the study indicate that there is legal uncertainty in gross split profit sharing contracts, namely that there is overlap between regulations. The impact of using the gross split production sharing contract scheme has resulted in a production sharing value in the terms & conditions contained in the gross split production sharing contract scheme which is considered less competitive for contractors in terms of providing access to gross revenue. The implementation of the gross split profit sharing contract scheme must be accompanied by a simplification of the number of regulations governing the gross split. Too many, frequently changing, and complicated regulations will lead to legal uncertainty. Keywords: legal certainty; gross splits; investment.